Industry engagement with control research: Perspective and messages. (2020) - Samad, Tariq; Bauer, Margret; Bortoff, Scott; Di Cairano, Stefano; Fagiano, Lorenzo; Odgaard, Peter Fogh; Rhinehart, R. Russell; Sánchez-Peña, Ricardo; Serbezov, Atanas; Ankersen, Finn; Goupil, Philippe; Grosman, Benyamin; et al.
Abstract: Despite the enormous benefit that has accrued to society from control technology and the continued vitality of control science as a research field, there is broad consensus that the practitioners of control and the academic research community are insufficiently engaged with each other. We explore this concern with reference to the oft-cited theory/practice gap but also from an industry perspective. The core of this article is comprised of ten "messages, " intended primarily for researchers interested in the practical impact of their work, that we hope shed insight on the industry mindset. Results from surveys and other data are cited to underpin the points. Some educational synergies between industry and academia are also noted. To highlight the continuing relevance of control science to industry, several recent examples of successful, deployed advanced control solutions are presented. The authors of this article are members of the IFAC Industry Committee, formally established in 2017 with objectives that include (per the updated IFAC Constitution) "increasing industry participation in and impact from IFAC activities."